FORM OF PARENTS' PREVENTION MEASURES ON CYBERBULLYING BEHAVIOR IN ADOLESCENTS - Lintang Dwi Aprilia; Shabilla Noor Rachma (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
This paper covers the forms of cyberbullying prevention measures in adolescents. Cyberbullying is sometimes still underestimated by some people, even though the impact of this cyberbullying will have a huge impact on teenagers. This study aims to describe several forms of cyberbullying prevention measures at the age of teenagers. The object of this research is the parents of teenage children. This study uses a quantitative method approach that will use an inductive mindset to conclude. Then, using a questionnaire for data collection methods. From the data collected through filling out the google form, it can be concluded that the form of parental action taken to prevent cyberbullying behavior is by providing education about social media to children, often communicating with children, and emotionally supporting children such as giving love. to children, applying time restrictions on the use of gadgets and in using social media to children, conducting social media checks. As well as telling children that they have to sort out what I should post on social media. Keywords:   Emotional Regulation, Group Counseling, Sociodrama